REDUPLIKASI BAHASA INGGRIS DAN BAHASA TONTEMBOAN ( SUATU ANALISIS KONTRASTIF ) - RATAG, LIDIA ELVINA; KODONG, FENTJE; RAMBING, ROSALINA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2019)
ABSTRACT            This study is an attempt to describe and analyze the English and Tontemboan language specifying on the process of reduplication and the contrast of both languages to find the similarities and differences interms of forms analyzing. The English data have been collected from several English books, dictionary, thesis, related theories from library, internet, whereas the Tontemboan data are collected from informants and internet. The descriptive method is used to describe and analyze the reduplication of both language by using theory of Jensen (1990:68), Ramlan (2009:63), Keraf (1987:120), Quirk and Greenbaum (1973). After describing the process of reduplication of English and Tontemboan language, the writer makes a contrastive analysis to finding out the similarities and differences of both language by using Lado’s theory.  Theoritically this investigation is going to give a contribution in morphological analysis especially on reduplication, for development of  linguistics at the faculty of Humanities Sam Ratulangi University. The result of this investigation shows that English has full reduplication with phonemic variation. Whereas Tontemboan language has a full reduplication, partial reduplication, and reduplication with affixation. Keywords : Reduplication, English and Tontemboan Language, Contrastive Analysis